2017
DOI: 10.3791/55520
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mesenchymal-Epithelial Transitions in Sarcoma Cells

Abstract: Phenotypic plasticity refers to a phenomenon in which cells transiently gain traits of another lineage. During carcinoma progression, phenotypic plasticity drives invasion, dissemination and metastasis. Indeed, while most of the studies of phenotypic plasticity have been in the context of epithelial-derived carcinomas, it turns out sarcomas, which are mesenchymal in origin, also exhibit phenotypic plasticity, with a subset of sarcomas undergoing a phenomenon that resembles a mesenchymal-epithelial transition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Interestingly, all four tested mammalian cell lines revealed Mn-dominated echo-detected field swept (EDFS) spectra with comparable intensity per cell (Figure S7, Table S3). However, we found that HEK cells are advantageous for the electroporation experiments because of easy growth and less adherent architecture as compared to other tested lines, which allows for easier handling and shorter recovery time. , …”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, all four tested mammalian cell lines revealed Mn-dominated echo-detected field swept (EDFS) spectra with comparable intensity per cell (Figure S7, Table S3). However, we found that HEK cells are advantageous for the electroporation experiments because of easy growth and less adherent architecture as compared to other tested lines, which allows for easier handling and shorter recovery time. , …”
mentioning
confidence: 83%
“…We show that four different mammalian cell lines exhibit comparable intracellular manganese concentrations; therefore, the achieved sensitivity is also expected for other mammalian cells. However, we found that HEK cells are particularly suited for electroporation experiment because their weak adhesion to the culture plastic dish , facilitates handling of the sample and analysis after shorter recovery times. Notably, suspension HEK cell line derivatives are also available, e.g., HEK293-F, , which could offer further advantages for in-cell EPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial‐mesenchymal transition (EMT) is a process in which epithelial cells acquire mesenchymal features 20 . In cancer, EMT is associated with tumour initiation, invasion, metastasis 21‐23 . Many studies had shown that EMT was associated with invasion and metastasis of thyroid cancer and lateral cervical lymph node metastasis 24‐26 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regulation of EMT is a complex process that is tightly regulated in different biological events. Epithelial-to-mesenchymal transition is a reversible process, and therefore in certain circumstances mesenchymal-to-epithelial transition (MET) can also take place, particularly during oncogenic processes [ 3 , 4 , 5 ]. Regulatory mechanisms driving MET fall beyond the scope of the present review (see for excellent reviews on MET [ 6 , 7 , 8 ]).…”
Section: Introductionmentioning
confidence: 99%